Disorders of Mineral and Bone Metabolism in Patients with Crohn's Disease - C. Von Westarp; A.B.R. Thomson; T.R. Overton; R.M. Rogers; P.E. Hodges; V.L. Fornasier; P.M. Crockford (Canadian Journal of Gastroenterology)
Crohn's disease is known to produce malabsorption of calcium and vitamin D which affect the skeleton. A variety of techniques were used to assess the prevalence of mineral and bone abnormalities in 53 consecutive patients with Crohn's disease. Twenty healthy controls were compared with 28 men and 25 women with Crohn's disease. In males, the mean corrected serum calcium concentration was elevated, the mean winter plasma 25-hydroxyvitamin D was low, as was the bone volume on biopsy and the fractional absorption of {7Ca. In females, the corrected serum calcium was also higher than in controls, as was the serum alkaline phosphatase activity. The female patients had significant decreases in both summer and winter plasma vitamin D levels, metacarpal cortical thickness and fractional absorption of 47Ca. The disturbances in bone and mineral metabolism were generally mild and were not associated with use of glucocorticosteroids but were more severe in patients with a history of bowel resection. Thus, patients with Crohn's disease are at risk of developing metabolic bone disease and consideration should be given for an assessment of the skeleton in patients with Crohn's disease. especially in women and in patients with previous ilea! resection. A battery of tests may be needed to exclude the diagnosis of metabolic bone disease but a 25-hydroxyvitamin D assay and hand x·rays using industrial grade film are recommended as a valuable preliminary assessment.